EPISTEMOLOGI PENDIDIKAN PANCASILA DI ERA DISRUPSI: KONSEP PENGETAHUAN BENAR DALAM TES KEMAMPUAN AKADEMIK PANCASILA 2026 SERTA IMPLIKASINYA TERHADAP IDENTITAS GLOBAL CITIZEN - Az Zahra, Putri Salma; Diva Fitria Kusumawardani; Gilang Aditya Nugroho; Hanum Kholifah Ramadhani; Intan Amalia Putri; Muhammad Hafis Hari Alfarizi (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2026)
Advances in information technology in this era of disruption are transforming the way society acquires and evaluates the truth of knowledge. This situation demands that civic education be grounded in a strong epistemological foundation, particularly in Pancasila education, which emphasizes not only cognitive aspects but also moral and national values amid globalization and the post-truth phenomenon. This study aims to analyze the concept of "true knowledge" from the perspective of the philosophy of science, its relevance to the design of the 2026 Pancasila Academic Ability Test (TKA), and its implications for the formation of a global citizen's identity. The study employs a qualitative approach through a literature review method, utilizing relevant books and journal articles. Data were analyzed using content analysis techniques to identify key ideas related to the concept of true knowledge in civic education. The results indicate that true knowledge must be rational, scientifically accountable, and aligned with the values of Pancasila. This concept is relevant to the design of the 2026 Pancasila Academic Ability Test (TKA), which emphasizes critical thinking, digital literacy, and argumentative reasoning to foster a generation of global citizens without losing their national identity.